Expanding the Concept of G Protein-Coupled Receptor (GPCR) Dimer Asymmetry towards GPCR-Interacting Proteins - Kamal, Maud (MDPI, 2011)
G protein-coupled receptors (GPCRs), major targets of drug discovery, are organized in dimeric and/or oligomeric clusters. The minimal oligomeric unit, the dimer, is composed of two protomers, which can behave differently within the dimer. Several examples of GPCR asymmetry within dimers at the level of ligand binding, ligand-promoted conformational changes, conformational changes within transmembrane domains, G protein coupling, and most recently GPCR-interacting proteins (GIPs), have been reported in the literature. Asymmetric organization of GPCR dimers has important implications on GPCR function and drug design. Indeed, the extension of the “asymmetry concept” to GIPs adds a new level of specific therapeutic intervention.